Efektifitas Kerja sama Antara Pihak Sekolah dan Puskesmas dalam Pemberian Layanan Kesehatan di Taman Kanak-kanak - Dilla AT, St. Hajar; Asqia, Nurul; Musakkir, Hazrah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
Health in Early Childhood is very important so that children can grow and develop optimally. This research aims to determine the effectiveness of collaboration between the community health center and the school in providing health services at Aisyiyah Kindergarten. The method used in this research is descriptive qualitative research method. The collection techniques used were interviews and documentation. The results of the research show that the collaboration between the community health center and the school has been running for around 5 years. The type of service provided by the puskesmas is the administration of vitamin A and worm medicine twice a year. According to him, the health services provided by the puskesmas at PAUD institutions are effective.